L-arginina em dietas contendo ou não produto lácteo para leitões desmamados - Bem, Francisco Aldevan Miranda (2018)
The objective was to evaluate the supplementation of L-arginine in diets containing or not milk product for weaned piglets. For this purpose, we used 32 piglets weaned at 21 days of same commercial line, with average weight of 1.919 ± 5.159 kg, distributed in a random block design to control the initial weight differences. The experimental diets were: DS - Diet mainly composed of corn soybean meal without dairy product; DSA - Diet consisting mainly of corn soybean meal without dairy product with supplementation of 0.6% of L-arginine; DL - Diet composed mainly of corn soybean meal with dairy product; DLA - Diet consisting mainly of corn soybean meal with dairy product and supplementation of 0.6% of L-arginine. When the animals reached 43 days of age, one animal from each experimental plot was slaughtered. The productive performance, incidence of diarrhea, glycemic curve, intestinal morphometry, immunohistochemistry, relative organ weight, hepatic glycogen, serum parameters and economic viability were evaluated. The supplementation of 0.6% of L-arginine in diets without or with dairy product increased (P <0.05) the daily weight gain and the final weight of piglets from 21 to 32 days. There was a reduction in the incidence of diarrhea in piglets fed diets with 0.6% of L-arginine, whether or not containing dairy products. In relation to the intestinal morphometry of the animals, it was verified that in the diets containing milk product and 0.6% of L-arginine presented higher (v <0.05) relation villus: crypt. It was also observed in immunohistochemistry, lower rate of mitosis and apoptosis in the jejunum of animals that received dairy diets. On the other hand, the non-dairy diet, when supplemented with 0.6% arginine, increased the serum concentrations of IgA and IgG compared to the non-supplemented. (P <0.05). It is concluded that dietary supplementation of 0.6% of L-arginine promoted an increase in immune activity of weaned piglets at 21 days, improved intestinal integrity and consequently reduced daytime diarrhea. Arginine may mitigate the deleterious effect of whole-plant diets for weaned piglets.